Pengaruh Pengalaman Magang, Kompetensi Mahasiswa Dan Lingkungan Kerja Terhadap Minat Menjadi Akuntan Publik - Kartina Muliasari; Sari Andayani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to examine, demonstrate, and analyze the influence of internship experience, students' competence, and work environment on the interest of accounting students in state universities in Surabaya to become public accountants. This research uses primary data in the form of a questionnaire. The sample used consisted of 93 respondents, with sample determination using the proportionate stratified random sampling method. The analytical method used in this research is multiple linear regression analysis with the assistance of the SPSS program for calculations. The results of this research indicate that internship experience does not have an influence on the interest of accounting students to become public accountants, while students' competence and work environment have an influence on the interest of accounting students to become public accountants.